How to thrive in the virtual workplace : simple and effective tips for successful, productive and empowered remote work - Glazer, Robert (CEO); Sloan, Mick. (London : Bluebird, 2021)
The business world was already gravitating toward virtual workplaces, even before COVID-19 created the largest remote work experiment in history. Suddenly organizations as big as Twitter were learning their employees didn't need an office in order to get great results. This is something Robert Glazer has known for over a decade. In the highly actionable How to Make Virtual Teams Work, Glazer taps into his experience managing a virtual office - and winning twenty "best places to work" awards - while providing leaders with a step-by-step playbook on how to intentionally build a remote workforce and culture by developing core values that provide guidance in hiring talent who works well remotely, creating comprehensive onboarding plans, using technology to communicate and connect with remote employees, and more. This goes way beyond a typical HR strategy book. By employing these specific strategies, leaders can build a remote environment that thrives and make it one of their key competitive advantages. The remote work revolution is here - the leaders who will build the future are the ones who can lead top performing virtual teams. Learn how to build a world-class organization - office no longer required.
Introduction -- Part One: Thriving as a Remote Employee -- 1. Remote Working: What's It All About? -- 2. Getting the Most out of Remote Work -- Part Two: Thriving as a Remote Organization -- 3. It Starts with Culture -- 4. What starts Well -- 5. Setting Your Team Up for Success -- 6. Bringing People Together -- Conlusion.
Keywords: Telecommuting; Virtual work teams